The Influence of Creativity and Family Support 0n the Entrepreneurial Interests of Generation Z in Bandar Lampung - Risnanda Febriani; Iskandar Ali Alam (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
The aim of this study is to examine how creativity and family support influence the entrepreneurial interests of Generation Z in Bandar Lampung City. This study applies quantitative methods and purposive sampling techniques involving 100 respondents. Data was collected. It was collected through questionnaires. The data was then analysed. The analysis used multiple linear regression, taking into account classical assumption tests. The results of the study indicate that the variables of creativity and family support influence entrepreneurial interest simultaneously. This study shows that creativity and family support are complementary factors in shaping the entrepreneurial interest of Generation Z.